Buriti oil microencapsulation in chickpea protein-pectin matrix as affected by spray drying parameters - Moser, Poliana [UNESP]; Ferreira, Sungil [UNESP]; Nicoletti, Vânia Regina [UNESP] (Elsevier, 2019)
The present study aimed to evaluate the influence of atomization and drying conditions in microencapsulation of carotenoids using chickpea protein (CP) and high-methoxyl pectin (HMP) complexes. The dimensionless numbers Weber (We) and Ohnesorge (Oh) and shear rate were calculated and related to atomization performance in the spray drying. The influence of drying temperature (154–196 °C) and feed flow rate (1.2–6.8 mL/min) on process yield (PY), moisture, carotenoid retention (CR), encapsulation efficiency (EE), color, particle size distribution and morphology of microparticles were investigated. The We values varied from 424.1 to 425.4, while Oh was a constant value (0.24). These numbers indicated that the emulsion was properly atomized in the spray dryer. The increase in shear rate at the nozzle caused a decrease in PY and lower CR. The temperature had a positive effect on PY, while the feed flow rate had a negative effect. The CR was higher in the high and low drying rates, while the lowest CR was observed at the central point. In general, the powder moisture was low (0.19–0.57%), the EE was high (82–92%), the particle diameter varied from 13 to 22 μm and the microparticles presented a morphology adequate for protecting the carotenoids.
Keywords: Atomization; Electrostatic interaction; Encapsulation; Mauritia flexuosa; Ohnesorge number; Weber number